PENGARUH LEVEL DIVERSIFIKASI, JUMLAH SEGMEN, DAN JENIS SEKTOR INDUSTRI TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 â€“ 2018 - Felicia; Rizka Indri Arfianti (Jurnal Akuntansi, 2020)
The high competition in the business world with many competitors has forced the company to develop its business, one of them by diversification. This study aims to investigate the influence of diversification level, segment numbers, and industrial sector types on firm performance measured by the excess value. The theory underlying this research is agency theory, which describes the relationship between the company owner with the company management, The number of samples of this study are 333 companies from miscellaneous industry sector, and consumer goods sector, and basic industry and chemicals sector listed on the Indonesia Stock Exchange throughout 2017 â€“ 2018. The results showed that data can be pooled for 3 years, all classic assumption tests are fulfilled, and partial regression coefficient test found that variable diversification level and variable number of segments > 0.05, then Ho1 and Ho2 rejected, while type of miscellaneous industry sector and Type of consumer goods sector <0.05, then Ho3 and Ho4 received. The conclusion showed that variable diversification level and variable number of segments has not sufficient evidence of negative effect on excess value, while type of miscellaneous industry sector and Type of consumer goods sector sufficient evidence of negative effect on excess value. Keywords: Firm Performance, Diversification Level, Number of Segments, and Industrial Sector. References: Amyulianthy, R., & Nuraini, Sari. (2013), â€œPengaruh Diversifikasi Terhadap Kinerja Perusahaanâ€, Binus Business Review, Vol.4, no.1, pp.215â€“230. Berger, P. G., & Eli, O. (1995), â€œDiversificationâ€™s Effect on Firm Valueâ€, Journal of Financial Economics, Vol.37, pp.39â€“65. Bowerman, B. L., Oâ€™Connell, R. T., & Murphree, E. S. (1979), Business Statistics in Practice, Edisi 7, New York: McGraw-Hill/Irwin. Chandra, D., & Triyani, Y. (2015), â€œPengaruh Level Diversifikasi, Leverage, Return On Asset, Umur Perusahaan, Dan Sektor Industri Terhadap Nilai Perusahaan Yang Terdaftar Di BEI Periode 2009-2011â€, Jurnal Akuntansi Manajemen, Vol.4, no.2, pp.66â€“84. Cooper, D. R., & Schindler, P. S. (2013), Business Research Methods, Edisi 12, New York: McGraw-Hill. 'Diversifikasi Usaha, Unilever Masuk Bisnis Saus Sambal' (2018), CNBC Indonesia, 28 September, diakses 9 Oktober 2019, https://www.cnbcindonesia.com/market/20180928100757-17-35152/diversifikasi-usaha-unilever-masuk-bisnis-saus-sambal Ghozali, I. (2013), Aplikasi Analisis Multivariette Dengan Program IBM SPSS 23, Edisi 8, Semarang: Badan Penerbit Universitas Diponegoro. Gujarati, D., & Dawn, P. (2009), Basic Econometrics, Edisi 4, New York: McGraw-Hill. Harto, P. (2005), â€œKebijakan Diversifikasi Perusahaan Dan Pengaruhnya Terhadap Kinerja: Studi Empiris Pada Perusahaan Publik Di Indonesiaâ€, SNA VIII Solo, pp.297-307. Ikatan Akuntan Indonesia (2014), Standar Akuntansi Keuangan, Jakarta: Salemba Empat. Jensen, M. C., & William, H. M. (1976), "Theory of The Firm: Managerial Behavior, Agency Cost and Ownership Structure", Journal of Financial Economic, Vol.3, No.4, pp.1-75. Kamus Besar Bahasa Indonesia. 2014. â€œKamus Besar Bahasa Indonesia Onlineâ€, diakses 5 Oktober 2019 http://www.kbbi.web.id. Kieso, D. E., Weygandt, J. J., & Warfield, T. D. (2016), Intermediate Accounting, Edisi 16, John Wiley and Sons, Inc. Lucyanda, J., & Wardhani, R. H. K. (2017), â€œPengaruh Diversifikasi Dan Karakteristik Perusahaan Terhadap Kinerja Perusahaanâ€, Jurnal Riset Akuntansi dan Keuangan. Montgomery, Cynthia A. (1994), Corporate Diversification, Journal of Economic Perspectives, Vol.8, No.3, pp.163-178. Rani, P. (2015). â€œPeran Kepemilikan Manajerial Dalam Memoderasi Pengaruh Strategi Diversifikasi Terhadap Kinerja Perusahaanâ€, Jurnal Akuntansi dan Keuangan, Vol.4, no.2, pp.162â€“82. Salindeho, A. O., Ivonne, S. S., & Joubert, B. M. (2018), â€œPengaruh Diversifikasi Usaha Terhadap Kinerja Keuangan Dan Return Saham Study Kasus Pada Perusahaan Manufaktur Automotive and Effect of Business Diversification of Financial Performance and Return Stock Case Stock in Automotive and Component Manufacturingâ€, Jurnal Riset Akuntansi dan Keuangan, Vol.6, no.3, pp.1078â€“87. Sari, I. A., Wiratno, A., & Suyono, E. (2014), â€œPengaruh Strategi Diversifikasi Dan Karakteristik Perusahaan Terhadap Kinerja Perusahaanâ€, JAFFA (Journal of Auditing, Finance, and Forensic Accounting), Vol.02, no.1, pp.13â€“22. Scott, W. R. (2015), Financial Accounting Theory, Edisi 7, Toronto: Pearson Canada Inc. Setionoputri, A., Meiden, C., & Siagian, D. (2007), â€œPengaruh Diversifikasi Korporat Terhadap Excess Value Perusahaan Manufaktur, Perdagangan Grosir Dan Eceran, Serta Properti Dan Real Estate Yang Terdaftar Di BEI Tahun 2005-2007â€ Bidang Akuntansi Private: Akuntansi Keuangan dan Pasar Modal, pp.1â€“25. Satoto, S. S. (2009), â€œStrategi Diversifikasi Terhadap Kinerja Perusahaanâ€, Jurnal Keuangan dan Perbankan, Vol.13, no.2, pp.280â€“287. Spence, M. (2002), â€œSignaling in Retrospect and the Informational Structure of Marketsâ€, American Economic Review, Vol.92, no.3, pp.434â€“459. Thompson, A. J. G., & Peteraf, M. (2012), Crafting and Executing Strategy: Concept and Cases, Edisi 18, New York: McGraw Hill. Virginia, Y. M., & Ratnasih, C. (2017), â€œPengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Produktivitas Kerja Dan Berimplikasi Pada Kinerja Karyawanâ€, Journal of Chemical Information and Modeling, Vol.53, no.9, pp.1689â€“99. Wolk, H. I., Dodd, J. L., & Tearney, M. G. (2003), Accounting Theory: Conceptual Issues in a Political and Economic Environment, Edisi 6, Mason: South-Western College Pub.